Неизвестная личинка жука-листоеда рода Chrysolina (Coleoptera, Chrysomelidae) с Кавказа - Охрименко, Н.В. (Вестник зоологии, 1993)
A description of the previously unknown larva of Chrysalina abschasica — rare endemic species, with data on bionomy and ecology. Material is deposited in the Institute of Animal Evolutionary Morphology and Ecology, Russian Academy of Sciences (Moscow).